2019
DOI: 10.31234/osf.io/pc6zh
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hand preference and Mathematical Learning Difficulties: New data from Greece, the United Kingdom, and Germany and two meta-analyses of the literature

Abstract: Objective: Increased rates of atypical handedness are observed in groups of neurotypical individuals who are low-performing in mathematical tasks as well as in individuals with special educational needs, such as dyslexia and autism. This is the first series of studies and meta-analyses to investigate whether elevated levels of atypical handedness are also to be found in individuals with Mathematical Learning Difficulties (MLD). Method: We report three new studies (N = 134; N = 1,899; N = 149) and two sets of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 133 publications
(175 reference statements)
1
4
0
Order By: Relevance
“…Our findings are in line with previous findings that do not show elevated levels of atypical (left, mixed, or non-right) handedness in a condition not affecting language, namely mathematical learning difficulties (Papadatou-Pastou et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are in line with previous findings that do not show elevated levels of atypical (left, mixed, or non-right) handedness in a condition not affecting language, namely mathematical learning difficulties (Papadatou-Pastou et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…The Role of Handedness in Arithmetic Processing. Behaviourally, there is no clear evidence for general performance differences between marked right-handers and left-handers in math 33 , although both right-and left-handers usually perform better than for example mixed-handers [34][35][36] . However, somewhat contrary to the above findings, professional mathematicians show on average a lower degree of handedness 37,38 .…”
mentioning
confidence: 96%
“…Moreover, the authors suggested that deaf individuals who acquired language (either sign or spoken) at a later age are those who present with increased rates of atypical handedness. A possible reason could be that increased rates of left-and/or mixed-handedness seem to be specifically associated with conditions related to impaired language-related abilities (Papadatou-Pastou et al, 2019). This is in line with the finding that higher genetic risk for ADHD and genetic liability towards lower intelligence and educational years have been associated with reduced language-related skills (Verhoef et al, 2019) and left-handedness, while there is no association between handedness and genetic factors involved in bipolar disorder (Schmitz et al, 2021).…”
Section: Discussionmentioning
confidence: 99%